COVID-19 Vaccine Framing: The Case of Astrazenca and Twitter Users - Alkhammash, Reem (International Journal of Language and Literary Studies, 2023)
Framing of health messages on social media can impact health choices and behaviour such as vaccine uptake. The present study aimed to examine how AstraZeneca has been framed on social media, characterize Twitter users who have engaged in the distribution of health-related information about the AstraZeneca vaccine, and demonstrate the impact of various frames on user engagement. Tweets with a collective total of more than 159,000 words were gathered from tweets posted during the second and third week of March 2021 and analyzed using a cognitive linguistics approach, i.e., frame semantics. In addition, social media mining tools were employed to investigate user engagement. The findings indicate the presence of negative vaccination framing with three sub-systems: the vaccine (i.e., vaccination politics), the government’s response to (in)effectiveness, and citizens (the vaccinated), which are known through public reaction. All frames represented AstraZeneca in a negative light and have implications for health professionals, policies, and practices. Furthermore, Twitter user analysis revealed a link between the condensed nature of the retweets about the AstraZeneca vaccine and the potential spread of health misinformation. The findings inform future research by providing a snapshot of how the public has dealt with recent news of the reported side effects of the AstraZeneca vaccine on social media. The study concludes that the findings provide useful information in understanding the impact of health messages on social media in influencing people’s vaccine uptake.